Effects of Weed-Free Periods on Organic Romaine Lettuce Production. Issue 1 (2nd January 2018) - Parry, Sarah; Shrestha, Anil
ABSTRACT: Weed management in Romaine lettuce (Lactuca sativa L. var. longifolia) is an economic challenge for organic farmers. This study evaluated the effect of weed-free durations on crop yield and quality, weed densities and biomass, and weeding time in two growing seasons. Treatments included weedy entire-season; weed-free for 7 days after transplanting (DAT), 14 DAT, 21 DAT, 28 DAT, 35 DAT, 42 DAT; and weed-free entire season (49 DAT). Weeds were removed by hand-hoes and the time taken to weed each plot was recorded. Weed densities were recorded prior to each weeding and weed biomass was recorded at crop harvest. Total and marketable lettuce heads were recorded and crop quality was estimated. Weed interference up to 21 DAT resulted in approximately 45% total and 58% marketable yield loss. Weed control beyond this period did not result in significant (p < 0.05) increases in crop yield and quality. However, weed densities at the end of the season were 4- to 15-fold and weed biomass approximately 18-fold greater in plots kept weed-free only for 21 DAT compared with plots kept weed-free season-long. This suggested that weed seed-return may be a concern if late-season weeding is not conducted. To minimize weed seed-return, the plots would have to be kept weed-free for about 35 DAT. However, labor costs must be taken into consideration because the time required to hand-hoe was approximately 87 hr ha −1 person −1 greater in plots kept weed-free for 35 DAT compared with plots kept weed-free for 21 DAT.